Severe Arboviral Neuroinvasive Disease in Patients on Rituximab Therapy: A Review - Kapadia, Ronak K; Staples, J Erin; Gill, Christine M; Fischer, Marc; Khan, Ezza; Laven, Janeen J; Panella, Amanda; Velez, Jason O; Hughes, Holly R; Brault, Aaron; Pastula, Daniel M; Gould, Carolyn V (Clinical infectious diseases, 2023)
With increasing use of rituximab and other B-cell depleting monoclonal antibodies for multiple indications, infectious complications are being recognized. We summarize clinical findings of patients on rituximab with arboviral diseases identified through literature review or consultation with the Centers for Disease Control and Prevention. We identified 21 patients on recent rituximab therapy who were diagnosed with an arboviral disease caused by West Nile, tick-borne encephalitis, eastern equine encephalitis, Cache Valley, Jamestown Canyon, and Powassan viruses. All reported patients had neuroinvasive disease. The diagnosis of arboviral infection required molecular testing in 20 (95%) patients. Median illness duration was 36 days (range, 12 days to 1 year), and 15/19 (79%) patients died from their illness. Patients on rituximab with arboviral disease can have a severe or prolonged course with an absence of serologic response. Patients should be counseled about mosquito and tick bite prevention when receiving rituximab and other B-cell depleting therapies.